Draft Sixth Five year Plan (1978-83) Volume III Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1978)
This scheme envisages strengthening the establishment of survey and Land Records for completing the Revenue Survey and Settlement Operation in the remaining areas of Andaman District and the whole area covered by Nicobar District. Village mans and other land records showing the lend already allotted, land reserved for nistar purposes and vacant land available for future allotment to landless persons developmental activities etc. will be prepared after conducting the field survey. The issue of khatuni sips(patta) to the tenants which is a part of survey operation will enable the. cultivators including tribals to avail loan from banks for agriculture purposes. Revision of Revenue Survey and Land Records in South Andaman will be done.
Andaman and Nicobar Administration
Government of India Planning Commission
Keywords: Panchayats; Land Reforms; Andaman and Nicobar Administration; Miscellaneou; Civil works; Electrical & Mechanical works; Slum improvement Clearance; urban and rural planning; Andaman public Works Department; Generatiohof employment anticipated